THE PLIO-QUATERNARY MAGMATISM OF SOUTHERN TUSCANY AND NORTHERN LATIUM: COMPOSITIONAL CHARACTERISTICS, GENESIS AND GEODYNAMIC SIGNIFICANCE - Peccerillo, Angelo; Poli, Giampiero; Donati, Carmelita (Ofioliti, 2007)
Southern Tuscany has been traditionally considered as a typical crustal anatectic magmatic province. However, extensive petrological and geochemical investigations carried out in the last years revealed a much more complex magmatic setting given by the occurrence of a large variety of rock types. The main rock associations are represented by: 1) acid volcanics and intrusives of crustal anatectic origin; 2) Ultrapotassic rocks with lamproitic (LMP) affinity; 3) Hybrid rocks between LMP and Roman-type (ROM) potassic and highly potassic magmas; 4) High-potassium calcalkaline (HKCA) and shoshonitic (SHO) magmas. Acid anatectic rocks are generally associated and mixed with mafic lavas and enclaves of variable composition. LMP, HKCA, SHO, and ROM-LMP hybrid magmas are of mantle origin. Their high enrichment in incompatible elements and the crustal-like isotopic signatures are consistent with a genesis in an anomalous upper mantle that was metasomatized by addition of subduction-related upper crustal material. However, variations of some key petrological and geochemical parameters reveal significant compositional heterogeneity of mantle beneath Tuscany. Petrological and geochemical data for mafic magmas suggest a complex evolutionary history of mantle sources, with at least two metasomatic events. These affected lithospheric and asthenospheric mantle, generating strong vertical and lateral compositional heterogeneity. The close similarity of Tuscany LMP rocks as those occurring in the Western Alps suggests that the earliest metasomatic modification was likely related to Alpine subduction processes. Younger mantle modifications occurred during subduction of the Adria Plate; this was responsible for the widespread Roman magmatism, but also produced some effects in the Tuscany province, as indicated by the occurrence of hybrids between Roman-type and lamproitic magmas.